ADAPTATION STRATEGIES AND IDENTITY FORMATION AMONG XINJIANG KAZAKHS IN KAZAKHSTAN - Saiken, Ayikailin (Nazarbayev University School of Sciences and Humanities, 2022)
When shared ethnicity is not enough for co-ethnic migrants to adapt and integrate into the co-ethnic society, considerations of different post-migration adaptation methods and identity formation among Kazakh 'repatriates' of different origins are essential. The thesis focuses on the adaptation strategies and identity formation of Xinjiang Kazakhs. It examines how the social/cultural capital gained in China helps Xinjiang Kazakhs find jobs in local Kazakh society and form their identity. I implement the survey questionnaires and semi-structured interviews. As an insider, I also use the semi autoethnography method partly supplement the main results. The main finding indicates that, for Xinjiang Kazakhs, Chinese language skills, social networks, and knowledge gained from China or related to Chinese culture, as their unique cultural and social capital, help them adapt to local Kazakhstan society and help them to find a job. The secondary finding shows that Xinjiang Kazakhs have a hybrid identity; their perceptions of their homeland are torn between their birthplace in China and their living place in Kazakhstan. While some still struggle with feeling 'in-between,' many of them create the 'third' space, defining themselves as 'global citizens
Keywords: Type of access: Restricted; Kazakh repatriate; Xinjiang Kazakhs; China